PENGEMBANGAN BAHAN AJAR KOMIK BERBASIS PROBLEM BASE LEARNING DENGAN ADOBE PHOTOSHOP - Yasinta Lisa; Florentina Rahayu Esti Wahyuni; Tirsianus Tirsianus (STKIP Persada Khatulistiwa Sintang, 2020)
ABSTRACTThis study aims to determine the feasibility of problem-based learning comics using Adobe Photoshop software in learning respiratory system material in humans. Development techniques refer to the 4-D model (Define, Design, Development & Disseminate). 1 material expert, 1 media expert, 1 biology teacher were assessed for its eligibility, then conducted a limited trial. Collecting research data using expert assessment questionnaires and test questions. The results of the validation of the media expert of 81.63% were categorized as Very Good and the results of the validation of the material experts by 88.53% were categorized as Very Good. The results of feasibility by users of biology teachers were 86.66% categorized as Very Good and the results of eligibility by student users were 82.2% categorized as Very Good. The results of different tests with paired t test obtained t count = 23.057 with sig (p) = 0.000. Obtained t count ≥ t table (2.069) and p <0.05, it can be concluded that there are significant differences in learning before and after using comics and comics, this is feasible and interesting to develop.Keywords: Comics, Problem Based Learning, Learning OutcomesABSTRAKPenelitian bertujuan untuk mengetahui kelayakan komik berbasis problem based learning menggunakan software adobe photoshop pada pembelajaran materi sistem pernapasan pada manusia. Teknik pengembangan merujuk pada model 4-D (Define, Design, Development & Disseminate). Komik dinilai kelayakannya oleh 1 Ahli Materi, 1 Ahli Media, 1 Guru Biologi, kemudian melakukan uji coba terbatas. Pengumpulan data penelitian menggunakan angket penilaian ahli dan soal tes. Hasil validasi ahli media sebesar 81,63% dikategorikan Sangat Baik dan hasil validasi ahli materi sebesar 88,53% dikategorikan Sangat Baik. Hasil kelayakan oleh pengguna guru biologi sebesar 86,66% dikategorikan Sangat Baik dan hasil kelayakan oleh pengguna siswa sebesar 82,2% dikategorikan Sangat Baik. Hasil uji beda dengan uji t berpasangan diperoleh t hitung = 23,057 dengan sig (p) = 0,000. Diperoleh t hitung ≥ t tabel (2,069) dan p < 0,05, maka disimpulkanKata Kunci: Komik, Problem Based Learning, Hasil Belajar